Islamic Legal Views on the Equality of Days in Determining the Beginning and End of Ramadan (Isbat Session) - Devina Arifani (International Journal of Law Society Services, 2025)
Determining the beginning and end of Ramadan is an important aspect in the implementation of fasting for Muslims which has a strong basis in the Al-Qur'an and the hadith of the Prophet Muhammad.ﷺ. In general, the methods used in this determination are divided into two main approaches: rukyatul hilal (direct observation of the crescent moon) and hisab (astronomical calculations). Differences in the use of these methods often lead to differences in determining the start and end of Ramadan among various Muslim communities. This study aims to analyze Islamic legal views on efforts to standardize days in determining the start and end of Ramadan through the Isbat Session mechanism. The method used in this study is a qualitative approach with library research, by reviewing classical and contemporary literature relevant to the fiqh (Islamic jurisprudence) for determining prayer times. The results show that normatively, Islam allows for differences in methods for determining the start of the month, as long as they are based on valid evidence. However, in the context of national life, the Isbat Session organized by the government is an important instrument in integrating the results of rukyat and hisab to achieve uniformity in determining the days. From an Islamic legal perspective, there is a fiqh principle of hukmul hakim yarfa'ul khilaf which emphasizes that government decisions can eliminate differences of opinion for the common good. Some scholars support the unification of days as a means of maintaining the unity of the Muslim community and adherence to the ulil amri (leaders in authority). On the other hand, others maintain the legitimacy of differences based on the concepts of ikhtilaf and differences in matla' (reasoning). Therefore, a moderate approach offers a solution by emphasizing tolerance for differences while promoting unity through official state authority. Therefore, the unification of days in determining the beginning and end of Ramadan is not an absolute obligation in classical fiqh, but rather a contextual necessity in modern society to maintain social harmony and unity among Muslims.